Enhancing English Learning for Elementary Students Through Children's Songs - Tuhfatul Mubarokah Assalamah (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
Learning and teaching activities occur almost every day in the classroom between teachers and students. In this context, the process is usually thought of as the teacher delivering material to students while the students listen to the teacher's explanation. Learning in the classroom can occur if an interaction or synergy is created from various factors that support the teaching and learning process such as the presence of teachers, students, curriculum, teaching methods or techniques, teaching media and others. In this case, a learning activity is carried out to achieve learning objectives. This study aims to investigate the effectiveness of using children's songs as a method of learning English in elementary schools. The research method used is qualitative research with a literature study approach. The research results show that the use of children's songs in English learning in elementary schools can increase students' motivation, strengthen their language skills, and facilitate enjoyable learning. Children's songs help students internalize English vocabulary, grammar and intonation more effectively. These findings provide important insights for the development of English language learning strategies that focus on students' active involvement. It is hoped that the results of this research can become a basis for developing a more innovative and student-oriented English language learning approach in elementary schools.